Use of multiparametric magnetic resonance imaging and fusion‐guided biopsies to properly select and follow African‐American men on active surveillance. (26th June 2019) - Bloom, Jonathan B.; Lebastchi, Amir H.; Gold, Samuel A.; Hale, Graham R.; Sanford, Thomas; Mehralivand, Sherif; Ahdoot, Michael; Rayn, Kareem N.; Czarniecki, Marcin; Smith, Clayton; Valera, Vladimir; Wood, Bradford J.; et al.
Abstract : Objectives: To determine the rate of Gleason Grade Group (GGG) upgrading in African‐American (AA) men with a prior diagnosis of low‐grade prostate cancer (GGG 1 or GGG 2) on 12‐core systematic biopsy (SB) after multiparametric magnetic resonance imaging (mpMRI) and fusion biopsy (FB); and whether AA men who continued active surveillance (AS) after mpMRI and FB fared differently than a predominantly Caucasian (non‐AA) population. Patients and methods: A database of men who had undergone mpMRI and FB was queried to determine rates of upgrading by FB amongst men deemed to be AS candidates based on SB prior to referral. After FB, Kaplan–Meier curves were generated for AA men and non‐AA men who then elected AS. The time to GGG upgrading and time continuing AS were compared using the log‐rank test. Results: AA men referred with GGG 1 disease on previous SB were upgraded to GGG ≥3 by FB more often than non‐AA men, 22.2% vs 12.7% ( P  = 0.01). A total of 32 AA men and 258 non‐AA men then continued AS, with a median (interquartile range) follow‐up of 39.19 (24.24–56.41) months. The median time to progression was 59.7 and 60.5 months, respectively ( P  = 0.26). The median time continuing AS was 61.9 months and not reached, respectively ( P  = 0.80). Conclusions: AA men were more likely to be upgraded from GGG 1 on SB to GGG ≥3 on initial FB; however, AA and non‐AA men on AS subsequently progressed at similar rates following mpMRI and FB. A greater tendency for SB to underestimate tumour grade in AA men may explain prior studies that have shown AA men to be at higher risk of progression during AS.